2022
DOI: 10.1080/08897077.2021.1944955
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Screening Brief Intervention Referral to Treatment (SBIRT) Training on Health Professional Trainees’ Regard, Attitudes, and Beliefs toward Patients who use Substances

Abstract: Background: Screening Brief Intervention Referral to Treatment (SBIRT) was developed as an integrated and comprehensive public health approach that includes early screening and intervention to address substance use in a variety of health care settings. Research suggests that SBIRT is effective in reducing substance use in individuals whose use places them at higher risk for negative health and social consequences. However, less is known about how training in SBIRT modifies attitudes, regard, and beliefs toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Pre-post studies with SBIRT training as the intervention (6 studies) found mixed results among trainees (and in 1 study with HCPs) 30,34–36,38,47 . Two studies found reductions in stigma, 34,47 whereas 1 study found no change 38 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pre-post studies with SBIRT training as the intervention (6 studies) found mixed results among trainees (and in 1 study with HCPs) 30,34–36,38,47 . Two studies found reductions in stigma, 34,47 whereas 1 study found no change 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Pre-post studies with SBIRT training as the intervention (6 studies) found mixed results among trainees (and in 1 study with HCPs) 30,34–36,38,47 . Two studies found reductions in stigma, 34,47 whereas 1 study found no change 38 . In 3 studies that used multiple stigma scales or looked at stigma against multiple conditions, findings were mixed between SUD and stigma scales 30,35,36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this study, the MCRS will be split into three separate questionnaires which assessed midwives' attitudes towards women who use alcohol, tobacco and illicit drugs while pregnant respectively. The scale has been used previously and has been validated for use in nursing and midwifery contexts [29,30].…”
Section: Medical Condition Regard Scale (Mcrs)mentioning
confidence: 99%